Pengenalan Internet of Thing pada anak-anak Panti Asuhan Tiara Putri Korpri - drantantiyas, nike dwi grevika; Suaif, Ahmad; Gani, Ferizandi Qausar; Khourinisa, Vera; Putra, Septia Eka Marsha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M), Institut Teknologi Sumatera, Lampung, Indonesia., 2025)
The purpose of this community service activity is to introduce the Internet of Things to children, particularly those in orphanages. The extraordinary development of digital communication technology offers significant positive impacts when properly understood. The method implemented is a knowledge transfer approach, which includes lectures and dialogues, along with examples of commonly used applications. The evaluation was conducted by dividing the participants into two groups: children and teenagers. For the children, the evaluation method involved a question-and-answer session with the success parameter being the number of participants raising their hands. For the teenagers, a pre-test and post-test consisting of multiple-choice questions were administered. The results were quite remarkable, with the success rate for the children reaching 62.5% and the teenagers nearly 88%, proving that the material was very well absorbed.